1988
DOI: 10.1007/bf01784375
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of plasminogen activators by human colorectal and gastric tumor explants

Abstract: Conditioned media from explants of human colorectal and gastric tumors in short-term organ culture were analysed for plasminogen activator activity, activity toward the synthetic urokinase substrate, Spectrozyme-UK, and for the presence of urokinase antigen using monospecific goat antibody, by enzyme-linked immunosorbent assay. Comparisons were made between primary tumors, adjacent normal mucosa and metastatic lesions. These analyses were carried out on unfractionated culture fluids and on fractions obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 19 publications
2
12
0
1
Order By: Relevance
“…This hypothesis is consistent with previous findings where a lower proteolytic uPA activity was determined in the metastases compared to primary tumors [37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…This hypothesis is consistent with previous findings where a lower proteolytic uPA activity was determined in the metastases compared to primary tumors [37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…Our results confirmed the earlier report of total-and u-PA activity or antigen level being significantly higher in primary gastric cancer tissues than in normal mucosae (Harvey et al, 1988;Nishino etal., 1988). The predominant type of activator in lung, colon and breast cancers was demonstrated by Markus et al (1983) to be of the urokinase type.…”
Section: Discussionsupporting
confidence: 95%
“…Conversely, inhibition of uPA can reduce the invasion and metastasis in H-ras-transformed NIH3T3 cells (Axelrod et al, 1989;Rao et al, 1993). It has also been reported that inhibition of uPA can reduce the size of prostate cancer tumors or even cause complete remission of cancers in SCID mice (Harvey et al, 1988;Jankun et al, 1997). These ®ndings provide direct evidence for a causal role for uPA in local tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 62%